Peningkatan Kemampuan Menulis Cerita Anak Bagi Guru TK Kecamatan Rumbio Jaya - Alvi Puspita; Raja Syamsidar; TM Sum (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2022)
The Science and Technology Program for the Community (IbM) that the team carried out was Improving the Ability to Write Children's Stories for Kindergarten Teachers in Rumbio Jaya District. The target to be achieved is to increase the ability to write children's stories for kindergarten teachers in Rumbio Jaya District in order to participate in the National Literacy Movement. The methods used by the team to achieve these targets were lecture, question and answer and practice methods. The results found that of the 12 training teachers, only four people submitted their writings.